Addressing Individual Values to Impact Prudent Antimicrobial Prescribing in Animal Agriculture - Redding, Laurel E.; Brooks, Cecilia; Georgakakos, Christine B.; Habing, Greg; Rosenkrantz, Leah; Dahlstrom, Michael; Plummer, Paul J. (Frontiers in Veterinary Science, 2020)
Antimicrobial resistance is a growing public health threat driven by antimicrobial use – both judicious and injudicious - in people and animals. In animal agriculture, antimicrobials are used to treat, control, and prevent disease in herds of animals. While such use generally occurs under the broad supervision of a veterinarian, individual animals are often treated by farm owners or managers. The decision to administer antimicrobials is therefore influenced not only by the clinical situation but also by the motivations and priorities of different individual actors. Many studies have examined the drivers of external forces such as costs, workload and time constraints, or social pressures on antimicrobial use by veterinarians and producers, but none have explored the role of individually held values in influencing decision-making related to antimicrobial use. Values are deeply held normative orientations that guide the formation of attitudes and behaviors across multiple contexts. Values have been shown to be strongly tied to perceptions of and attitudes towards polarizing topics such as climate change, and preliminary evidence suggests that values are also associated with attitudes to antimicrobial resistance and stewardship. In this article, we draw on lessons learned in other fields (human health care, climate change science) to explore how values could be tied to the extrinsic and intrinsic factors that drive antimicrobial use and prescribing in animal agriculture. We also provide suggestions for ways to build a bridge between the veterinary and social sciences and incorporate values into future research aimed at promoting antimicrobial stewardship in animal agriculture.